Appraisal of a new scheme for prenatal screening for Down's syndrome. Issue 6785 (11th May 1991) - Sheldon, T A; Simpson, J
Abstract : OBJECTIVE--To appraise a new method of prenatal screening for Down's syndrome based on maternal serum concentrations of alpha fetoprotein, unconjugated oestriol, and human chorionic gonadotrophin combined with maternal age--the "triple test." DESIGN--Examination of the cost effectiveness of the triple test relative to screening only by maternal age over a range of population detection rates. SETTING--Leicestershire Health Authority. MAIN OUTCOME MEASURES--Costs per affected fetus detected. RESULTS--The triple test is more cost effective than screening only by maternal age for risk cut off points for amniocentesis, resulting in a detection rate over 45%. The most efficient detection rate is around 60-65%, for which the cost per case detected is around 29, 000 pounds, through screening with higher detection rates is still likely to be cost beneficial. CONCLUSIONS--Prenatal screening for Down's syndrome based on the triple test should replace screening based only on maternal age. Individual women's preferences should be elicited by the use of structured decision analysis in order to maximise utility and so increase the benefits of the screening programme.